SOCIAL MARKETING COMMUNICATION STRATEGY OF TAMAN READING MASYARAKAT "ALAM RIANG" IN IMPROVING LITERACY CULTURE IN THE CHILDREN OF JOMBANG ISLAMIC BOARDING SCHOOL VILLAGE - Ningrum, Retno Via; S.S., M.A., Tsuroyya (The Commercium, 2023)
Marketing strategy is one of the efforts to deliver a program introduced in the community with the aim of changing people's behavior for the better. Marketing strategy is said to be one of the basics to provide real activities in everyday life. This study aims to determine the social marketing communication strategy of the Alam Riang Community Reading Park in improving literacy culture in the children of Pesantren Jombang village. This research uses a qualitative approach and a case study method. The data collection method was carried out by interviewing 5 informants consisting of the founder of the Alam Riang Community Reading Park, Members of the Alam Riang Community Reading Park, parents of Alam Riang students, Alam Riang students and observing literacy activities. The results showed that the social marketing communication strategy seen in improving literacy culture consists of product, promotion, presentation and personnel so that it can be known the communication strategy used by TBM Alam Riang